Changes in plant responses induced by an arthropod influence the colonization behavior of a subsequent herbivore - Silva, Diego B.; Jiménez, Alejandro; Urbaneja, Alberto; Pérez-Hedo, Mertixell; Bento, José Maurício Simões (Wiley Online Library, 2021)
Background: Plants in nature can be sequentially attacked by different arthropod herbivores. Feeding by one arthropod species may induce plant-defense responses that might affect the performance of a later-arriving herbivorous species. Understanding these interactions can help in developing pest-management strategies. In tomato, the sweet-potato whitefly Bemisia tabaci and the two-spotted spider mite Tetranychus urticae are key pests that frequently cohabit on the same plant. We studied whether colonization by one species can either facilitate or impede later colonization of tomato plants by conspecific or heterospecific individuals. Results: B. tabaci females showed a strong preference for and increased oviposition on plants previously colonized by conspecifics. In contrast, plants infested with T. urticae repelled B. tabaci females and reduced their oviposition rate by 86%. Although females of T. urticae showed no preference between conspecific-infested or uninfested plants, we observed a 50% reduction in the number of eggs laid on conspecific-infested plants. Both herbivorous arthropods up-regulated the expression of genes involving the jasmonic acid and abscisic acid pathways, increasing emissions of fatty-acid derivatives, but only B. tabaci increased the expression of genes related to the salicylic acid pathway and the total amount of phenylpropanoids released. Terpenoids were the most abundant compounds in the volatile blends; many terpenoids were emitted at different rates, which might have influenced the arthropods' host selection. Conclusion: Our results indicate that B. tabaci infestation facilitated subsequent infestations by conspecifics and mites, while T. urticae infestation promoted herbivore-induced resistance. Based on both the molecular and behavioral findings, a novel sustainable pest-management strategy is discussed.